Jet vectoring using secondary Coanda synthetic jets - Ryota KOBAYASHI (The Japan Society of Mechanical Engineers, 2020)
In recent years, studies on the fundamental principle of thrust vectoring using jets have been conducted to realize next-generation aircraft applications. Various methods for vector control of jet flow have been proposed, such as methods that achieve control via steady, continuous jets under the Coanda effect, steady suction flows near the Coanda surface, and synthetic jets from a neighbor slot as secondary jets. However, there are no studies on the flow direction control of jets using the secondary synthetic Coanda jet. In this study, the influence of synthetic jets near a circular cylinder on the flow characteristics of a primary jet was experimentally investigated. The main results obtained in the study were that the direction of the primary jet flow can be controlled using the secondary synthetic jet, and the degree of jet deflection depends on the frequency of the velocity oscillation for the secondary synthetic jet under an identical momentum ratio. Furthermore, when using the synthetic jet as the secondary flow, a controllable region larger than that obtained when using a steady and continuous injection or suction flow is expected. This is because secondary flow is generated using the ratio of the momentum between the primary jet and the secondary flow at the slot exit in conjunction with the dimensionless frequency of the synthetic jet based on the velocity of the primary flow at the slot exit.